A case study of trauma narrative for civil engineering students on hydrometeorological disaster victims in Malaysia - Chong S.T.; Ng Y.J.; Chow M.F.; Rahman A.Z.A.; Loh K.S.; Karthikeyan J. (IEEE Computer Society, 2023)
Curricula; Engineering education; Engineers; Students; Civil engineering students; Dam construction; Engineering programmes; Human being; Malaysia; Malaysians; Natural disasters; Theoretical framework; Disasters